The Changing Relationship Between the Government and the Nonprofit Sector in Iceland - Ómar H. Kristmundsson (2009)
Fræðigrein The paper illustrates a historical examination of nonprofit relations in welfare services in Iceland. Variables affecting the conditions under which different types of relations are developed are defined. The findings from the Icelandic case study coincide with other international studies describing some general changes in government-nonprofit relations in the 20th century, from supplementary to more complex complementary and adversarial relations using Young’s conceptualization. There are, however, some distinguishing features. The supplementary phase was prolonged when compared to other countries and nonprofits’ leading role in public policy making and provision of welfare services more prominent. A small and reactive public administration can be considered an important explanatory factor. Governmental effort to define a formal contractual relationship in the spirit of new public management at the end of the century have seemingly not lead to fundamental changes in the partners’ interaction.